5 - Esclavage et traite des esclaves dans les manuels de l’enseignement secondaire du Sénégal - Ibrahima Seck, (Afrika Zamani, 2022)
This paper focuses on the issue of slavery and the slave trade as it has been implemented in the History programs of the secondary school system in Senegal. It analyzes the contents of those programs throughout the colonial period up to their last version issued in 2004, and looks at their connections with the historical knowledge so far produced by African historians. Last but not least, this paper also raises some methodological issues related to the way of linking Academic production with school textbooks. African historians have, in the part, favored a victimizing approach to the issue of slavery and have eschewed to highlight the local systems of domination such as domestic slavery and the making of captives on African soil and destined to the Transatlantic slave trade. This approach has generated ‘forbidden knowl- edge’ comparable to what the colonizers have defined in order to domesticate African minds. Nevertheless, an increasing number of African historians are in- vestigating the issue of slavery in Africa despite a quite hostile environment where the holders of the new historical approach are sometimes depicted as trai- tors to the African cause. The African communities have, more than ever before, a vested interest in integrating into the education of their children, essential information and knowledge that can assist in clarifying issues and breaking the vicious cycles of violence, marginalization and poverty.